REPRESENTASI FEMINISME DAN KRITIK SOSIAL ATAS PERAN PEREMPUAN DALAM “YUNI 2021” (STUDI ANALISIS SEMIOTIKA MODEL ROLLAND BARTHES) - Sekar Pawestri (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
This study focuses on the analysis of the representation of feminism and social critique of women's roles depicted in the film "Yuni" (2021) using Roland Barthes' semiotic approach. The objective of this research is to identify and evaluate how issues of feminism and social critique regarding gender roles are communicated through symbolism and signs in the film. The research method used is Barthesian semiotic analysis, where the film is analyzed based on connotation, denotation, and mythology derived from visual and textual signs.The results of the study show that the film "Yuni" significantly features feminist themes, such as women's struggle for freedom and equality in a patriarchal society. Moreover, the film also provides a social critique of the norms that restrict women's roles. The conclusion of this research is that "Yuni" makes an important contribution to the discourse on feminism and social critique through its strong representation and deep narrative about women's lives in Indonesia.